Insights into the global genomic features of Salmonella enterica serovar Gallinarum biovars Gallinarum and Pullorum - Campos, Isabela C [UNESP]; Vilela, Felipe Pinheiro; Saraiva, Mauro De M. S [UNESP]; Junior, Angelo Berchieri [UNESP]; Falcão, Juliana Pfrimer (Oxford University Press (OUP), 2024)
Aims: Characterize global genomic features of 86 genomes of Salmonella Gallinarum (SG) and Pullorum (SP), which are important pathogens causing systemic infections in poultry. Methods and results: All genomes harbored efflux pump encoding gene mdsA and gold tolerance genes golS and golT. Aminoglycoside (aac(6′)-Ib, aadA5, aph(6)-Id, aph(3′')-Ib, ant(2′')-Ia), beta-lactam (blaTEM-1, blaTEM-135), efflux pump (mdsB), fosfomycin (fosA3), sulfonamide (sul1, sul2), tetracycline [tet(A)], trimethoprim (dfrA17), acid (asr), and disinfectant (qacEdelta1) resistance genes, gyrA, gyrB, and parC quinolone resistance point mutations, and mercury tolerance genes (mer) were found in different frequencies. Additionally, 310 virulence genes, pathogenicity islands (including SPI-1, 2, 3, 4, 5, 6, 9, 10, 12, 13, and 14), plasmids [IncFII(S), ColpVC, IncX1, IncN, IncX2, and IncC], and prophages (Fels-2, ST104, 500465-1, pro483, Gifsy-2, 103 203_sal5, Fels-1, RE-2010, vB_SenS-Ent2, and L-413C) were detected. MLST showed biovar-specific sequence types, and core genome MLST showed country-specific and global-related clusters. Conclusion: SG and SP global strains carry many virulence factors and important antimicrobial resistance genes. The diverse plasmids and prophages suggest genetic variability. MLST and cgMLST differentiated biovars and showed profiles occurring locally or worldwide.
Keywords: fowl typhoid; poultry; pullorum disease; Salmonella Gallinarum; Salmonella Pullorum; whole-genome sequencing